Coniacian sandstones from the North Sudetic Synclinorium revisited: palaeoenvironmental and palaeogeographical reconstructions based on trace fossil analysis and associated body fossils - Chrząstek, Alina; Wypych, Monika (Geologos, 2018)
The Coniacian quartz sandstones (Żerkowice Member, Rakowice Wielkie Formation) that crop out at quarries near Czaple-Nowa Wieś Grodziska (North Sudetic Synclinorium) contain a low-diversity assemblage of trace fossils: Gyrochorte isp., Ophiomorpha nodosa Lundgren, 1891, Ophiomorpha isp., Phycodes cf. curvipalmatum (Pollard, 1981), ?Phycodes isp., Planolites cf. beverleyensis (Billings, 1862), Thalassinoides paradoxicus Woodward, 1830 and ?Thalassinoides isp. Moreover, interesting compound burrow systems, here referred to as Thalassinoides-Phycodes cf. palmatus and ?Thalassinoides-Phycodes, were recognised at the Czaple Quarry. Additionally, ?Gyrochorte isp., Phycodes cf. flabellum (Miller and Dyer, 1878) and ?Treptichnus isp. were encountered at correlative levels in the Rakowice Małe Quarry. Some of these ichnotaxa have not been recorded previously from Coniacian sandstones of the Żerkowice Member. Additionally, in slabs of these sandstones, the gastropod Nerinea bicincta Bronn, 1836 and the bivalve Lima haidingeri Zittel, 1866 were found. These interesting finds, in particular the gastropods, were already noted from the study area in the first half of the twentieth century by Scupin (1912–1913. Ethologically, the trace fossil assemblage is represented by domichnia or domichnia/fodinichnia (Ophiomorpha, Thalassinoides), fodinichnia (Phycodes) and pascichnia (Gyrochorte, Planolites). The compound burrow systems (Thalassinoides-Phycodes) are interpreted as dwelling/feeding structures. The possible tracemakers are crustaceans (Ophiomorpha, Thalassinoides) or worm-like animals (annelids and other) (Planolites, ?Phycodes, Gyrochorte and ?Treptichnus). The assemblage of trace fossils is characteristic of the Skolithos ichnofacies and Cruziana ichnofacies, typical of shallow-marine settings. Ichnological studies, as well as the presence of accompanying fossils (bivalves, gastropods), confirm the palaeoenvironmental reconstruction of the Żerkowice Member sandstones by Leszczyński (2010). That author interpreted the Coniacian sandstones as bar and storm deposits laid down in a shallow epicontinental sea (mainly the foreshore-upper shoreface; up to the middle shoreface) under normal oxygenation and salinity, in soft substrate, above fair-weather wave base. The deposition of the Żerkowice Member sandstones is linked to a regression that started after uplift of the southeastern part of the North Sudetic Synclinorium.